DECISION – MAKING MODEL AND PRODUCTIVITY IN PUBLIC SECONDARY SCHOOLS IN ONDO NORTH SENATORIAL DISTRICT OF ONDO STATE, NIGERIA - Adeolu Joshua AYENI; Rita Titilayo OJO (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2022)
The dwindling level of teachers’ productivity in Nigerian secondary schools has been a matter of serious concern, which the education stakeholders perceived to be the aftermath effect of the inadequacies in principals’ decision-making strategies. This study therefore investigated the levels of principals’ decision-making strategies and determined the implication for productivity in secondary schools in Ondo North Senatorial District of Ondo State, Nigeria. Descriptive survey research design and ex-post facto research design were adopted. The sample comprised 150 school administrators and 600 teachers randomly selected from 30 public secondary schools. Data were collected using three research instruments titled “Principals’ Decision Making Strategies Questionnaire” (PDMSQ), “Teachers’ Productivity Questionnaire” (TPQ), and “Students’ Academic Performance Proforma” (SAPP). Four research questions and seven hypotheses guided the study. Research questions were analyzed using frequency count, and mean, while the hypotheses were tested using Multiple Regression Analysis and Pearson Product Moment Correlation (PPMC) at 0.05 level of significance. Results revealed that the consultation strategy (β = .644), collaborative strategy (β = .566), feedback strategy (β = .542) and corporate review strategy (β = .512) had the highest values and positive contributions to teachers’ productivity while the open door strategy had the least contribution to teachers’ productivity (β = .312) at p< 0.05. The result further indicated that there was a significant relationship between open door strategy and teachers’ productivity [r = 0.591>0.195], also there was a significant relationship between principals’ collaborative strategy and teachers’ productivity [r = 0.699>0.195], there was a significant relationship between consultation strategy and teachers’ productivity [r = 0.893>0.195], there was a significant relationship between feedback strategy and teachers’ productivity [r = 0.711>0.195], there was a significant relationship between corporate review strategy and teachers’ productivity [r = 0.698>0.195], and there was a significant relationship between principals’ decision-making strategies and students’ academic performance [r = 0.626 >0.195]. It was concluded that teachers’ involvement in decision-making is moderate and this accounted for the moderate level of teachers’ productivity and students’ academic performance. Based on the findings, it is recommended that the school principals’ should intensify efforts in the use of consultation, collaborative, feedback and corporate review strategies to enhance decision-making process while the State Ministry of Education should organize seminar/workshop to improve principals’ competence in the use of decision-making strategies to enhance teachers’ productivity in secondary schools. The dwindling level of teachers’ productivity in Nigerian secondary schools has been a matter of serious concern, which the education stakeholders perceived to be the aftermath effect of the inadequacies in principals’ decision-making strategies. This study therefore investigated the levels of principals’ decision-making strategies and determined the implication for productivity in secondary schools in Ondo North Senatorial District of Ondo State, Nigeria. Descriptive survey research design and ex-post facto research design were adopted. The sample comprised 150 school administrators and 600 teachers randomly selected from 30 public secondary schools. Data were collected using three research instruments titled “Principals’ Decision Making Strategies Questionnaire” (PDMSQ), “Teachers’ Productivity Questionnaire” (TPQ), and “Students’ Academic Performance Proforma” (SAPP). Four research questions and seven hypotheses guided the study. Research questions were analyzed using frequency count, and mean, while the hypotheses were tested using Multiple Regression Analysis and Pearson Product Moment Correlation (PPMC) at 0.05 level of significance. Results revealed that the consultation strategy (β = .644), collaborative strategy (β = .566), feedback strategy (β = .542) and corporate review strategy (β = .512) had the highest values and positive contributions to teachers’ productivity while the open door strategy had the least contribution to teachers’ productivity (β = .312) at p< 0.05. The result further indicated that there was a significant relationship between open door strategy and teachers’ productivity [r = 0.591>0.195], also there was a significant relationship between principals’ collaborative strategy and teachers’ productivity [r = 0.699>0.195], there was a significant relationship between consultation strategy and teachers’ productivity [r = 0.893>0.195], there was a significant relationship between feedback strategy and teachers’ productivity [r = 0.711>0.195], there was a significant relationship between corporate review strategy and teachers’ productivity [r = 0.698>0.195], and there was a significant relationship between principals’ decision-making strategies and students’ academic performance [r = 0.626 >0.195]. It was concluded that teachers’ involvement in decision-making is moderate and this accounted for the moderate level of teachers’ productivity and students’ academic performance. Based on the findings, it is recommended that the school principals’ should intensify efforts in the use of consultation, collaborative, feedback and corporate review strategies to enhance decision-making process while the State Ministry of Education should organize seminar/workshop to improve principals’ competence in the use of decision-making strategies to enhance teachers’ productivity in secondary schools.